MENINGKATKAN PEMBELAJARAN LOMPAT JAUH MELALUI PERMAINAN LOMPAT KATAK PADA SISWA KELAS V SD NEGERI 01 REMBUN KECAMATAN SIWALAN KABUPATEN PEKALONGAN TAHUN AJARAN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
Based on observations of the learning process at hletics, especiall y the long jump at the f if t h grade students of SDNegeri 01 Rembun Siwalan Pekalongan district has not gone wel l, because st udents are l ess chance of mot ion.From the descript i on of t he probl em, the authors strive to increase learning outcomes long jump t hrough aleapfrog game that aims to apply the concept of motion long j ump through a leapfrog game to add t o themot ion activit y of student s. So as to foster a sense of excitement and improve student l earning outcomes longj ump. This type of research is a classroom action research using practice tests. Subj ects were fifth grade st udentsof SD Negeri 01 Rembun who are 32 student s. Inst ruments used observation and observation test s. Dataanalysi s techniques used in this study is t he comparative descriptive stat i stics.Conclusions based on the result s of action research, l earning through play l eapfrog approach, can improvelearning outcomes long j ump. From the anal ysis of t he first cycl e is known percent age of 53.13% mast erylearning st udent number 17, in the second cycl e increased by 75%, wit h t he number of 24 student mastery.